KENDALA IMPLEMENTASI KEBIJAKAN FASILITASI ALAT PERAGA KAMPANYE PEMILU 2019 DI KOTA BUKITTINGGI - Rahmad, Riki; Asrinaldi, Asrinaldi; Indraddin, Indraddin (JURNAL SOSIAL POLITIK, 2020)
This study aims to analyze the factors inhibiting the implementation policy of the Campaign Props (APK) in Bukittinggi City. APK in the form of banners and billboards in the 2019 election campaign, many APKs that have been facilitated by the Election Commition  (KPU) are not installed in the designated zones and there are even election participants who do not utilize this APKs facilitation, even though the state funds used for this Facilities are quite large. This study uses descriptive qualitative research with a case study approach, data collection procedures in the form of interviews, observation and documentation. The theory used is the corten implementation model in which this Mode is based on the compatibility between the three elements that is program, implementation, and target group.  The results showed that election participants did not utilize the APK facility caused by (1) KPU rules regarding the size, design, and content of APKs are not in accordance with the perception of the election participants' persuasion needs (2) Political parties avoid conflicts with candidates considering that the APK content does not accommodate candidates photos (3) costs for installing and maintaining APKs are none from election participants. Judging from its effectiveness APK's facilitation policy in the 2019 elections in Bukittinggi City has not reached its goal. Inconsistency with the open proportional electoral system with the APK facilitation policy has several impacts in the campaign process, among others 1) competition between candidates in campaigning becomes uncompetitive  2) most APK facilitation held by KPU is largely unused